Arabic Vocabulary Learning Methods:An Overview of Conceptualisations in Journal Articles: طرق تعلم المفردات العربية :لمحة عامة عن المفاهيم في المقالات الصحفية - Muhammad Ivan Alfian; Sulton Firdaus; Muhammad Zakki Masykur; Meidias Abror Wicaksono (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2025)
Vocabulary is a crucial component of language acquisition and plays a key role in communicative competence. Mastery of Arabic vocabulary significantly influences overall language skills, making it essential for teachers to understand a variety of effective vocabulary teaching methods. This study aims to explore various Arabic vocabulary learning strategies by reviewing scientific articles published in Sinta 2 and Sinta 3 indexed journals between 2020 and 2024. The research employs a literature review method with a systematic approach based on Gough’s eight-step procedure. A total of 14 articles were analyzed to identify vocabulary learning strategies commonly applied. The findings reveal eight main methods: the use of mnemonic songs, Total Physical Response (TPR), sentence construction and writing techniques, language games, the Visual Auditory Kinesthetic (VAK) learning model, Think-Pair-Share strategy, cooperative learning, and imitation-based memorization. Additionally, the integration of digital tools such as Wordwall and online games proved to enhance vocabulary acquisition and learner motivation. These findings provide valuable insights for Arabic language teachers in selecting methods that align with learners’ characteristics and needs. The study recommends the adoption of varied and technology-supported approaches to improve the effectiveness of Arabic vocabulary learning.